RESPONS PERTUMBUHAN STEK TANAMAN VANILI (Vanilla planifolia Andrews) TERHADAP PEMBERIAN BERBAGAI INTENSITAS NAUNGAN DAN KOMBINASI MEDIA TANAM ORGANIK - Wahyuni, Ony Tri; Satria, Benni; Anwar, Aswaldi (Fakultas Pertanian, Universitas Janabadra, 2024)
This study aims to determine the appropriate paranet shade intensity and organic planting media combination for vanilla cuttings. The experiment was designed using a Split-Plot Design within a Completely Randomized Design. The shade intensities used are 50% and 70% of paranet. The organic planting media combinations are soil + compost + rice husk, soil + compost + cocopeat, soil + goat manure + rice husk, and soil + goat manure + cocopeat (in a 2:2:1 ratio, w/w). Data was analyzed using a F-test, followed by Duncan’s New Multiple Range Test at a significance level of 5%. The results indicate no interaction between paranet shade intensity and planting media combination. The 70% paranet shade intensity yields the best outcomes in terms of live cutting percentage (100%), shoot length (20.32 cm), internode length (3.24 cm), number of internodes (6.07), and leaf count (6.07 leaves). While different planting media may not significantly.